Education and the COVID-19 Pandemic: A Critical Discourse Analysis of Indonesian Merdeka Curriculum English Textbooks: Penelitian - Andi Sahtiani Jahrir; Edi Sam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the ideological construction of COVID-19 discourse within Grade XI English textbooks under Indonesia's Merdeka Curriculum. Employing Critical Discourse Analysis (CDA) based on Norman Fairclough's model, this research investigates how the textbooks represent social actors (government, health workers, citizens), actions, and values related to the pandemic. Analysis of a text titled